Influence of Herbage/Browse allowance on nutritive intake of cattle grazing a commiphora savannah in Kenya. - Mnene, W.N. (Texas A&M University, 1985)
This study was conducted in a commiphora savannah with two levels of bush canopy cover and two levels of herbage in august and December, respectively, in 1983 on the national range research station, kiboko, Kenya. Effects of season, available herbage, and bush level on dietary composition, preference, crude protein, digestible organic matter, and intake by cattle were determined. Diets were collected via oesophageally fistulated heifers while intake was estimated by the use of the external markers erbium and ytterbium orally administered daily to steers. Chloris roxburghiana, the most prevalent grass and sporobolus pellucidus produced more under high bush while cymbopogon pospochilii preferred open space. Availability of browse depended primarily on the shrub layer and was influenced by herbage level and precipitation. Treatment effects were influenced most by percent three-canopy cover. Cattle selected more grasses than browse of forbs in that order, regardless of bush level. More grass was selected in high herbage paddocks and during the dry season. Browse replaced grasses in all cases where grass consumption declined, particularly under low herbage level and during the wet season. Chloris roxburghiana, cymbopogon pospochilii and digitaria maeroblephana, and hermania alhiensis were the most dominate grasses and browse in the diets, respectively. Leaf fractions were the selected by cattle, especially in the high herbage paddocks and during the wet season. During the dry season under low herbage condition, cattle consumed recently shed dead browse leaves. Reduction of herbage mass led to selection of mopre dead and stemy material in the diets, and consumption of herbage relative to its availability, i.e., reduced preference. Selection of herbage relative to its availability, i.e. reduced preference. Selection of live material varied three fold between wet season and dry season trials. Season had a strong effect on dietary crude protein and energy intakes but had a strong effect on in vitro digestibility. Cattle had near or below maintenance level of crude protein and energy intake during the dry and beginning of the wet seasons, respectively. Digestibility was positively related to herbage level, the relationship being proportional. However, the influence of bush level on intake was inverse during the dry season. A drop in dietary digestibility required a similar drop in crude protein in order to effect a significant decline in intake.